EVOLUTION OF THE CURRENCY HEDGING INSTRUMENTS IN EMERGING MARKETS, CASE OF MOROCCO: ARE EXOTIC OPTIONS SUITABLE IN TERMS OF PRICE AND RISK COVERAGE? - Jabbouri, Imad; Benlafkih, Mehdi (European Scientific Journal, ESJ, 2014)
In this report, we will answer the problematic ―how the currency hedging instruments have evolved in Morocco, and how the implementation of exotic options would be beneficial and advantageous in terms of price and risk coverage‖. We will first analyze the different traditional financial instruments used in the Moroccan context. Afterwards, we will introduce the classical options present in Morocco from 2003. Subsequently, we will talk about the options of ―second generation‖ also called exotic options. Thereafter, we will compare the classical options with the exotic ones thanks to the results of a simulation. The simulation consists of two cases, the import and export case. Then, we will conclude by showing why exotic options should be implemented in Morocco.